2013
DOI: 10.1186/1748-717x-8-38
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of hypofractionated intensity modulated radiation therapy with concurrent and adjuvant temozolomide in patients with glioblastoma multiforme

Abstract: PurposeTo determine the safety and efficacy of hypofractionated intensity modulated radiation therapy (Hypo-IMRT) using helical tomotherapy (HT) with concurrent low dose temozolomide (TMZ) followed by adjuvant TMZ in patients with glioblastoma multiforme (GBM).Methods and materialsAdult patients with GBM and KPS > 70 were prospectively enrolled between 2005 and 2007 in this phase I study. The Fibonacci dose escalation protocol was implemented to establish a safe radiation fractionation regimen. The protocol de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…The observed lack of effect with DE in the current study is consistent with several other reports that have also failed to demonstrate a dose-response in tumor control and survival beyond conventional dose-schedules in patients with GBM. 17 , 18 With the exception of the study by Tsien et al that reported a median PFS and OS of 9 and 20.1 months, respectively, with DE radiotherapy (75 Gy delivered in 30 fractions), approximately half of the patients in that study still failed centrally. 19 …”
Section: Discussionmentioning
confidence: 96%
“…The observed lack of effect with DE in the current study is consistent with several other reports that have also failed to demonstrate a dose-response in tumor control and survival beyond conventional dose-schedules in patients with GBM. 17 , 18 With the exception of the study by Tsien et al that reported a median PFS and OS of 9 and 20.1 months, respectively, with DE radiotherapy (75 Gy delivered in 30 fractions), approximately half of the patients in that study still failed centrally. 19 …”
Section: Discussionmentioning
confidence: 96%
“…Some studies have found that participants who received HFR plus TMZ had comparable outcomes to those who received CFR. However, some studies have found that participants who received HFR had a better survival outcomes than those who received CFR (10, 36, 44, 45). A recent meta-analysis based on retrospective studies of the treatment of elderly patients (≥65 years) with GBM, found that participants who received HFR combined with TMZ had similar PFS to participants who received CRF plus TMZ, but that those who received HFR plus TMZ had a shorter OS (46).…”
Section: Discussionmentioning
confidence: 99%
“… 2 Although TMZ has slightly lower reported response rates compared to PCV, it has significantly improved toxicity profile with fewer than 10% of patients receiving TMZ developing a grade 3 or 4 hematologic toxicity compared to 50% of patients receiving PCV. 7 , 19 Speirs et al 20 studied 59 patients with anaplastic OG or anaplastic astrocytoma and reported superior OS with the use of radiation therapy and adjuvant TMZ among patients with 1p/19q codeletion (91% vs. 68% at 5 years, p =0.02), compared to patients without the chromosomal deletions. PFS was also improved but not statistically significant (70% vs. 46% at 5 years, p =0.10).…”
Section: Discussionmentioning
confidence: 99%